Intra and extra-hepatic cystadenoma of the biliary duct. Review of literature and radiological and pathological characteristics of a very rare case. (4th April 2012) - Soochan, Diana; Keough, Valerie; Wanless, Ian; Molinari, Michele
Abstract : Painless obstructive jaundice is often associated with a malignant disease of the common bile duct or head of the pancreas. The authors present a unique case of a 62-year-old woman affected by an intrahepatic cystadenoma that extended into the common biliary duct. To our knowledge no previous case reports have been published on similar cases. After undergoing an en-block hepatic and bile duct resection, this patient is doing well without signs of recurrent disease.